A Política cultural entre o Estado e o Mercado: a experiência brasileira de 2003 a 2006 - MELO, Carlos Alberto Barreto Campelo de (2022)
Throughout the Twentieth century structural changes in the capitalism system led the state to lose importance in the provision of cultural services in favor of the market mechanisms, which have become hegemonic. A process was set in motion that led to the incorporation of markets to cultural provision, which is clearly observed by contrasting welfare states and neoliberal regimes. This thesis focuses on cultural policy as it reflects the interplay of state and markets forces, and considers the Brazilian experience. In its initial stages, there occurred a n interaction of markets and cultural production, which to led to the emergence of what the Frankfurt School’ theorists called the cultural industry. Subsequently, this was greatly expanded. The same phenomenon can be observed in Brazil, which is reflected in new patterns of state intervention in the sphere of cultural policy, including the National Program of Support to Culture (Pronac). The thesis proposes a new concept to discuss these transformations, namely, which is based on the distinction between supply driven and demand driven programs. Neoliberal cultural policies adopt the former format – demand-driven. The thesis shows that private corporations and the main beneficiaries of the new cultural policies, because a com modification logic underlies their operation. The thesis considers the case of PRONAC under the Lula government as a prominent example of such neoliberal policies and shows on the basis of extensive research and primary data sources that the net result contrasts with the so-called administration’s social priorities.